Zur Einführung einer begrifflichen Perspektive in die Mathematik: Dedekind, Noether, van der Waerden1. Issue 3 (2nd September 2015) - Koreuber, Mechthild
Abstract: For the Introduction of a Conceptual Perspective in Mathematics: Dedekind, Noether, van der Waerden. „She [Noether] then appeared as the creator of a new direction in algebra and became the leader, the most consistent and brilliant representative, of a particular mathematical doctrine – of all that is characterized by the term ‚Begriffliche Mathematik'."2 The aim of this paper is to illuminate this "new direction", which can be characterized as a conceptual [begriffliche] perspective in mathematics, and to comprehend its roots and trace its establishment. Field, ring, ideal, the core concepts of this new direction in mathematical images of knowledge, were conceptualized by Richard Dedekind (1831–1916) within the scope of his number theory research and associated with an understanding of a formation of concepts as a "free creation of the human spirit"3 . They thus stand for an abstract perspective of mathematics in their entirety, described as 'modern algebra' in the 1920s and 1930s, leading to an understanding of mathematics as structural sciences. The establishment of this approach to mathematics, which is based on "general mathematical concepts" [allgemein‐mathematische Begriffe]4, was the success of a cultural movement whose most important protagonists included Emmy Noether (1882–1935) and her pupil Bartel L. van der Waerden (1903–1996). With the use of the term 'conceptual', a perspective is taken in the analysis which allows for developing connections between the thinking of Dedekind, the "working and conceptual methods" [Arbeits‐ und Auffassungsmethoden]5 of Noether as well as the methodological approach, represented through the thought space of the Noether School as presented under the term "conceptual world" [Begriffswelt]6 in the Moderne Algebra of van der Waerden. This essay thus makes a contribution to the history of the introduction of a structural perspective in mathematics, a perspective that is inseparable from the mathematical impact of Noether, her reception of the work of Dedekind and the creative strength of the Noether School.